Poloxamer 188 Attenuates Ischemia-Reperfusion-Induced Lung Injury by Maintaining Cell Membrane Integrity and Inhibiting Multiple Signaling Pathways - Shih-En Tang; Shih-En Tang; Wen-I Liao; Hsin-Ping Pao; Chin-Wang Hsu; Shu-Yu Wu; Kun-Lun Huang; Kun-Lun Huang; Shi-Jye Chu (Frontiers in Pharmacology, 2021)
Background: Poloxamer 188 (P188) possesses anti-inflammatory properties and can help to maintain plasma membrane function. P188 has been reported to exert beneficial effects in the treatment of various disorders. However, the effects of P188 in ischemia/reperfusion (IR)-induced acute lung injury have not been examined.Methods: We investigated the ability of P188 to attenuate IR-induced acute lung injury in rats and hypoxia/reoxygenation (HR) injury in murine epithelial cells. Isolated perfused rat lungs were exposed to 40 min ischemia followed by 60 min reperfusion to induce IR injury.Results: IR led to lung edema, increased pulmonary arterial pressure, promoted lung tissue inflammation and oxidative stress, and upregulated the levels of TNF-α, IL-6 and CINC-1, and increased Lactic dehydrogenase (LDH) activity in bronchoalveolar lavage fluid. IR also downregulated the levels of inhibitor of κB (IκB-α), upregulated nuclear factor (NF)-κB (NF-κB), and promoted apoptosis in lung tissues. P188 significantly suppressed all these effects. In vitro, P188 also exerted a similar effect in murine lung epithelial cells exposed to HR. Furthermore, P188 reduced the number of propidium iodide-positive cells, maintained cell membrane integrity, and enhanced cell membrane repair following HR.Conclusion: We conclude that P188 protects against lung IR injury by suppressing multiple signaling pathways and maintaining cell membrane integrity.